R&D funding and private R&D: Empirical evidence on the impact of the leading-edge cluster competition - Engel, Dirk (Springer Nature, 2020)
Abstract This paper analyzes the effects of the governmental ﬁnancing instrument Spitzencluster-Wettbewerb (Leading-Edge Cluster Competition, LECC) on R&D expenditure of ﬁrms in Germany. The LECC promotes cooperative research among business ﬁrms and research institutions under the umbrella of a common strategy, which is pursued by regional cluster organizations. We measure the effect of LECC funding on private R&D spending as well as the effects of the policy instrument on the composition of R&D (internal vs. external). Our analysis is mainly based on data from the R&D survey for Germany. We combine propensity score matching (to identify statistical twins) with a difference-in-differences estimator in order to measure the causal effects of the LECC. These results are complemented with the ﬁndings from expert interviews. Our results show that the LECC signiﬁcantly increases R&D expenditures in comparison to non-funded ﬁrms. On average, we did not ﬁnd evidence of crowding out. At the same time, we identiﬁed a greater leverage effect of the LECC for small and medium-sized ﬁrms. A comparison with companies that have been funded in other R&D-programs shows that the LECC leads to a greater increase in R&D expenditure in small and medium-sized enterprises (SMEs). The expert interviews in general conﬁrm these results and indicate that there are different patterns at ﬁrm level depending on ﬁrm size, strategy, and sector. In addition, they reveal that the effect of co-funding rules for R&D expenditure appears to be stronger for SMEs.